TRAINING BIMBINGAN KONSELING PELIMPAHAN PENGASUHAN ANAK PERSPEKTIF TAFSIR IBNU KATSIR DAN TAFSIR AL-MISHBAH DI KB MUSLIMAT MEDAN SATRIA, BEKASI - Badru Tamam; Malihah Malihah; Abd. Muid Nawawi; Andi Rahman; Baeti Rahman; Sarwanih Sarwanih (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2023)
This paper examines the delegation of childcare from the perspective of Tafsir Al-Mishbah and Tafsir Ibn Kathir. The study uses a qualitative method with text analysis to explore the major works of both thinkers. This involves a detailed analysis of verses 35-37 of Surah Ali Imran on the theme of delegation of childcare, followed by an analysis of the relevant Tafsir Al-Mishbah and Tafsir Ibn Kathir. The results of the study show that the delegation of parenting in Islam is a form of transfer of responsibility for caring for children that is allowed on condition that it complies with Sharia, especially maintaining the lineage and religion of the child. Tafsir Ibn Kathir emphasizes the obligation to fulfill the vow and the importance of kinship and spiritual protection of children in choosing caregivers, while Tafsir Al-Mishbah emphasizes the example of Prophet Zakariya as an ideal foster parent. Both commentaries agree on the urgency of vision, religious values, education, and security for children